2022
DOI: 10.3389/fmicb.2022.996834
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel metallo β-lactamase, SZM-1, in Shenzhen Bay, South China

Abstract: Metallo β-Lactamases (MBLs) degrade most clinical β-lactam antibiotics, especially Carbapenem, posing a huge threat to global health. Studies on environmental MBLs are important for risk assessment of the MBLs transmission among connected habitats, and between environment and human. Here, we described a novel metallo β-Lactamases, named SZM-1 (Shenzhen metallo-β-lactamase), from an Arenimonas metagenome-assembled genome recovered from the river sediment in the Shenzhen Bay area, south China. Phylogenetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Several studies have shown that there is an increase in the evolution and spread of MBL-producing bacteria in the non-hospital environment as reported in our study [5,7,20]. Furthermore, the results from our study corroborates to previous studies which have reported the prevalence of MBL-producing bacteria in livestock and poultry [7,11]. In this study, we detected the blaIMP-1 MBL genes in 3 P. aeruginosa isolates (6.3%) while the blaIMP-2 MBL genes were detected in 2 isolates of P. aeruginosa (4.2%) from poultry milieus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several studies have shown that there is an increase in the evolution and spread of MBL-producing bacteria in the non-hospital environment as reported in our study [5,7,20]. Furthermore, the results from our study corroborates to previous studies which have reported the prevalence of MBL-producing bacteria in livestock and poultry [7,11]. In this study, we detected the blaIMP-1 MBL genes in 3 P. aeruginosa isolates (6.3%) while the blaIMP-2 MBL genes were detected in 2 isolates of P. aeruginosa (4.2%) from poultry milieus.…”
Section: Discussionsupporting
confidence: 91%
“…Molecular analysis: PCR analysis for the detection of specific MBL genes (blaIMP-1, blaIMP-2, blaVIM-1, blaVIM-2) in the P. aeruginosa isolates that showed reduced susceptibility to any of the tested carbapenems (imipenem and meropenem) was performed in accordance to a previously used protocol [11,14,15]. DNA was extracted from the P. aeruginosa isolates using GENESpin DNA isolation kit (Eurofins, Hamburg) according to the manufacturer's guidelines.…”
Section: Ethicalmentioning
confidence: 99%
See 1 more Smart Citation